Activated carbons treated with sulphuric acid: catalysts for catalytic wet peroxide oxidation - Gomes, Helder (2010)
The commercial activated carbon Norit ROX 0.8 was subjected to different liquid phase treatments in order to produce activated carbons with varying surface chemistry and acid/base character. The prepared materials were used as catalysts in the catalytic wet peroxide oxidation of the acid dye Chromotrope 2R in order to assess their removal activity. Chemical characterization of the prepared materials includes determination of the point of zero charge and evaluation of the concentration and nature of acidic and basic surface functionalities by acid/base titrations and temperature programmed desorption. The relationship between the surface chemistry and efficiency for dye removal is discussed. In general, dye removal is increased when using catalysts with higher basic character, due to enhanced electrostatic attraction between the acid dye and the catalyst surface when compared with catalysts presenting acidic character. In addition, treatment with sulphuric acid introduces on the catalysts surface sulphur containing groups, which promotes the surface interaction between the pollutant and hydrogen peroxide. This leads to improved dye removal resulting from higher production of hydroxyl radicals close to the pollutant. Reutilization studies show that the catalyst prepared by sulphuric acid treatment is able to keep its performance in successive runs.